Lymphocyte cell population as a potential hematological index for early diagnosis of COVID-19 - Zhu, Yihua; Cao, XingJian; Lu, Yonghui; Xu, Dongsheng; Lu, Renfei; Li, Xinling (Cellular and Molecular Biology, 2020)
The pandemic diseases caused by SARS-CoV-2 are now threatening human health and survival. Early diagnosis and isolation of mild or asymptomatic COVID-19 patients is important to control the spread of SARS-CoV-2. In this study, we investigate the potential clinical utility of lymphocyte CPD for early diagnosis of COVID-19. To investigate the potential of lymphocyte cell population data (lymphocyte CPD) for use in early diagnosis of coronavirus disease 2019 (COVID-19). Lymphocyte CPD of healthy control (n = 51), common cold patients (n = 49) and mild COVID-19 patients (n = 126) were generated using hematology analyzer. The parameters were subjected to sensitivity and specificity analysis to determine their suitability as biomarkers for early diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Normality analysis showed that lymphocyte CPD followed a normal distribution. There were no significant differences in white blood cells (WBC) and lymphocyte (LY#) counts as well as the neutrophil-to-lymphocyte ratio (NLR) among the groups (p > 0.05). Lymphocyte volume standard deviation (LV-SD), lymphocyte conductivity standard deviation (LC-SD) and lymphocyte light scatter standard deviation (LS-SD) were significantly higher in the COVID-19 group than in common cold and control groups (p < 0.05). The corresponding mean lymphocyte light scattering (MLS) was significantly reduced in the COVID-19 group, relative to the common cold group, but was significantly increased, when compared with the control group (p < 0.05). Moreover, there was no significant difference in mean lymphocyte volume (MLV) between the COVID-19 group and the common cold or control group (p > 0.05), but it was significantly higher in the common cold group than in the control group (p < 0.05). At a cutoff value ≥ 16.38, LS-SD was more sensitive and specific than other lymphocyte CPD parameters. At a cutoff value ≥ 11.89, LC-SD achieved 84.4 % sensitivity, 87.5 % specificity, and an area under the curve (AUC) of 0.888. However, at a cutoff value ≥ 15.95, LS-SD reached 81.3 % sensitivity, 75 % specificity and an AUC of 0.876. These results suggest that lymphocyte CPD parameters have great diagnostic potential for SARS-CoV-2 infection and can be used for early diagnosis of the disease.